REVITALISATION OF MORAL VALUES IN MINANGKABAU CULTURE: PERSPECTIVE MODEL OF REALITY COUNSELING - Darimis Darimis (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Minangkabau loaded moral values​​ based on